PENGARUH LATIHAN INTERVAL PUKULAN TERHADAP HASIL SMASH PADA ATLIT OLAHRAGA BULUTANGKIS PB ASSHOFA PEKANBARU - Sukri, Muhammad; Zainur, Zainur; Nita Wijayanti, Ni Putu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this research is to see how the effect of interval training on smash results in PB badminton athletes PB ASSHOFA. It is known that athletes have the ability to play badminton less well, especially in doing smashes. This can be seen from the way students do smashes, punch techniques are still less sharp and directed. The elasticity of the athlete's waist is also still less visible than the student's body posture is still tense and less flexible. Coordination of the athlete's motion is still not good, thus reducing the punch result, this cause is caused by a lack of training methods to improve the quality of smash blows. The basic techniques in badminton are grip, footwork, service, under hand, over head, dropshot, netting. This type of research is an experiment. The purpose of this research was to determine the effect of interval training on smash results in PB Asshofa Pekanbaru badminton. The population in this research amounted to 17 people. The sampling technique is the sample aims (purposive sampling) so that a sample of 8 athletes from PB Asshofa Pekanbaru was obtained. The instrument carried out in this research is a forehand smash test, which aims to measure smash punch ability. After that, the data was processed with statistics to test the normality with the Liliefors test at a significant level of 0.05. The hypothesis proposed is the effect of interval punch training on smash results. Based on the results of the research, it can be concluded as follows, that there is the effect of interval training on the smash results on PB ASSHOFA Pekanbaru because, where t test analysis is obtained, the results of t count are 27.40 and t table is 1.860, H0 is rejected and H1 is accepted.Key Words: punch interval training, smash